Pauline Christianity : Luke-Acts and the legacy of Paul - Mount, Christopher N., 1962- (Supplements to Novum Testamentum ;, 2002)
A study of the composition and reception of Luke-Acts in relation to the category "Pauline Christianity" as it has been used to describe traditions, communities and persons connected to Paul. The inquiry is pursued along three lines and focuses on Paul's role in the history of early Christianity.